Primary Left Atrial Cardiopathy in Transthyretin Amyloidosis Cardiomyopathy by Multimodality Imaging: Implications for Thrombotic Events - Ozbay, Benay; Rearick, Corey; Satyavolu, Bharadwaj S; Soman, Prem; Wong, Timothy C; Starr, Matthew; Pillai, Bharat; Zhu, Jianhui; Azhar, Abdullah Z; Katz, William E; Sade, Leyla Elif (JACC. Cardiovascular imaging, 2025)
Thrombotic event (TE) risk is high in transthyretin amyloid cardiomyopathy (ATTR-CM). The authors sought to explore left atrial (LA) remodeling in ATTR-CM and its association with TE risk in comparison to other phenotypes of left ventricular hypertrophy (LVH). Subjects who underwent speckle tracking echocardiography, Tc-99m pyrophosphate scintigraphy, serum and urine immune electrophoresis, per registry protocol, were retrospectively identified (n = 405). Cardiac magnetic resonance and endomyocardial biopsy were used per clinical indication. Subjects with cardiac amyloidosis other than ATTR-CM were excluded, those with nonamyloid LVH served as controls. Propensity score matching was performed for age, sex, coronary artery disease, and diabetes. Longitudinal follow-up was performed over 5 years for TEs. In all ATTR-CM (n =149) and LVH (n =165) in a propensity matched cohort (104:104), ATTR-CM subjects had decreased left atrial reservoir strain (LASr), smaller left atrial volume index, more intense late gadolinium hyperenhancement, and increased LA stiffness as compared to LVH. In ATTR-CM, LASr correlated poorly with E/e', was severely depressed regardless of the diastolic dysfunction grade (in those with sinus rhythm), and did not correlate with left atrial volume index, in contrast to the LVH group. LASr and LA stiffness were associated with ATTR-CM independently of diastolic dysfunction and atrial fibrillation (AF) (OR: 1.2 and OR: 1.9, respectively; P < 0.001 and P = 0.002). Furthermore, LASr and LA stiffness were independently associated with TEs (n = 20) during follow-up, regardless of CHA DS -VASc or prevalent AF at baseline, in ATTR-CM. Primary LA cardiopathy seems to be associated with TEs in ATTR-CM, independently of AF, CHA DS -VASc, and LA dilatation, unlike other LVH phenotypes.